The Influence of Emotional and Rational Factors on Traders' Decision in Choosing Islamic Banking Services (Case Study of Traders at Baruga Market) - Wawan Wawan; Indra Nola; Lestari Daswan; Sitti Nur Annisa Amalia (Journal of Law and Economics, 2025)
This study aims to examine and analyze the influence of emotional and rational factors on traders' decisions in choosing Islamic banking services (case study of Baruga Market traders). This type of research is quantitative research. The data source in this study is primary data. The sample in this study amounted to 97 people taken using purposive sampling technique. The data collection technique used questionnaires distributed directly in the form of printed paper and Google from. Analyzed using multiple linear regression through SPSS software. The results of this study indicate that emotional factors have a significant influence on traders' decisions in choosing Islamic banking services (case study of Baruga Market traders), rational factors have a significant influence on traders' decisions in choosing Islamic banking services (case study of Baruga Market traders). As well as emotional factors and rational factors have a significant influence on traders' decisions in choosing Islamic banking services (case study of Baruga Market traders).